Psychophysiological and informational support of soldiers during combat operation - Belzetskyi, R. S.; Shyian, A. A.; Zlepko, S. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The scheme of acquisition, information processing and decision making in the management of combat operations is developed. The structure of the database for special unit soldiers and information communications system to predict the performance level of their combat tasks is given. The system of governance for the operation commander is suggested in the paper.